NON-MILITARY PERSONNEL DEVELOPMENT IN THE SECOND FLEET TOWARDS ORDERED ADMINISTRATIVE UNITS IN THE INDONESIAN NAVY - Ismaryanto, Andik; Ekowati, Masroro Lilik; Taufik, Wildan; Sudirman, Sudirman; Umiyati, Sri (JOURNAL ASRO, 2023)
Human resource development is an important activity because employees and institutions work together in a balanced manner for the company's existence. Human resource development is a unit of implementation of development and training, both career and organizational to increase individual and organizational effectiveness. Orderly and careful management of resources, facilities, and infrastructure is a guarantee for the establishment of a reliable Indonesian Armed Forces posture. because the Indonesian Armed Forces coaching system reflects a functional system that includes aspects of planning, organizing, implementing, and controlling aspects of subjects, objects, and methods. Provision of soldiers which is an activity to fill the Indonesian Armed Forces organization. To obtain the expected soldiering base, selected soldier candidates are educated at educational institutions according to the desired class and rank of soldier before being given a rank as legitimacy of authority, and responsibility in the soldiering hierarchy. The output produced in this study is the achievement of the implementation of Indonesian Armed Forces Non-Military Personnel Development in the second fleet which includes the dimensions of communication, resources, dispositions, and dimensions of the bureaucratic structure. Keywords: Effectiveness, Education, and Training Program, Indonesian Armed Forces Non-Military Personnel